The dispersal of protoplanetary discs – II: photoevaporation models with observationally derived irradiating spectra. Issue 2 (21st September 2021) - Ercolano, Barbara; Picogna, Giovanni; Monsch, Kristina; Drake, Jeremy J; Preibisch, Thomas
ABSTRACT: Young solar-type stars are known to be strong X-ray emitters and their X-ray spectra have been widely studied. X-rays from the central star may play a crucial role in the thermodynamics and chemistry of the circumstellar material as well as in the atmospheric evolution of young planets. In this paper, we present model spectra based on spectral parameters derived from the observations of young stars in the Orion nebula cluster from the Chandra Orion Ultradeep Project (COUP). The spectra are then used to calculate new photoevaporation prescriptions that can be used in disc and planet population synthesis models. Our models clearly show that disc wind mass loss rates are controlled by the stellar luminosity in the soft (100 eV to 1 keV ) X-ray band. New analytical relations are provided for the mass loss rates and profiles of photoevaporative winds as a function of the luminosity in the soft X-ray band. The agreement between observed and predicted transition disc statistics moderately improved using the new spectra, but the observed population of strongly accreting large cavity discs can still not be reproduced by these models. Furthermore, our models predict a population of non-accreting transition discs that are not observed. This highlights the importance of considering the depletion of millimetre-sized dust grains from the outer disc, which is a likely reason why such discs have not been detected yet.